(untitled) - Jefri Satria Andreas Sitorus; Sapta Aprilianto (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Evidence in criminal law is the most important thing in the judicial process. In the case of Jessica Kumala Wongso, there is electronic evidence device in the form of CCTV footage. It is necessary to conduct judicial review against the law regarding CCTV must be installed by the authorities. Aim: This study aims to analyze the validity and position of CCTV evidence device in the criminal proceedings. Method: This study used normative juridical writing by using three problem approaches, namely the case approach, the conceptual approach, and the statute approach. Result: The result of the study showed that the panel of judges in the cyanide coffee case still used CCTV as valid evidence, even though the Constitutional Court has declared that CCTV was not valid and could not be used as valid evidence in criminal justice process in Indonesia. Conclusion: Electronic evidence device could be used in the world of criminal law enforcement in Indonesia, because it still used interpretation in accordance with the Article 5 section (1) and section (2) of the Electronic Information and Transaction Law.